Air-drying and drying-rewetting effects in Japanese Andosols subjected to long-term organic rice farming. Issue 5 (2nd September 2020) - Kautsar, Valensi; Cheng, Weiguo; Tawaraya, Keitaro; Hattori, Satoshi; Yamada, Susumu; Kobayashi, Kazuhiko; Toriyama, Kazunobu
ABSTRACT: Paddy fields are generally submerged during the growing season and drained in the fallow season, and occasionally stimulating the air-drying effect and drying-rewetting effect on soil nitrogen (N) mineralization and soil carbon (C) decomposition. It is important to understand how these two effects take place in Andosol field under organic farming. To elucidate these effects, we incubated fresh, air-dried, and dried-rewetted paddy soil anaerobically under flooded condition. Soils were from the fields subjected to organic rice farming (ORF) for 4–5 years (4ORF), 8–9 years (8ORF), and 12 years (12ORF) with only rice residues and fallow weeds as organic matter applied, and cnventional rice farming (CRF). Soil samples were collected from plow layer of 0–15 cm depth after the rice harvest. The results showed that air-dried and dried-rewetted treatments could significantly increase N mineralization potential in 8ORF and 12ORF. The air-drying effects were not significantly changed in 4ORF, but significantly increased in 8ORF and 12ORF as compared to CRF. The drying-rewetting effects of C decomposition potentials were highest in 12ORF significantly. The N mineralization potential of air-drying effect showed no significant difference compared to drying-rewetting effect on conventional and organic rice farming. The ratio of C decomposition to N mineralization after 8 weeks incubation was higher in fresh soil (at 7.26–8.61) than those in air-dried (at 4.09–4.35) and dried-rewetted (at 3.94–4.26) soils. These indicated that the easily decomposable soil organic matter under the anaerobic flooded condition from fresh soil was changed by air-drying and drying-rewetting treatments. The slow increase of N mineralization and C decomposition with years of organic farming suggest the slow increase of fallow weed, the biomass of which gradually increase with years. The specific behavior of 12ORF soil suggest the transition of soil condition from a transitional state to an established state.